2010
DOI: 10.1016/j.jpainsymman.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Symptom Clusters, Eosinophils, and Survival in Hepatobiliary Cancer: An Exploratory Study

Abstract: Context The study of symptom clusters is gaining increased attention in the field of oncology in an attempt to improve the quality of life of patients diagnosed with cancer. Objectives The aims of the present study were to: (1) determine the prevalence and distribution of pain, fatigue, and symptoms of depression and their covariation as a cluster in people with hepatobiliary carcinoma; (2) characterize how variation in each individual symptom and/or their covariation as a cluster are associated with changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 59 publications
2
57
0
Order By: Relevance
“…In 10 of these papers (2,3,(48)(49)(50)(51)(52)(53)(54)(55), patients with cancer were evaluated. In the 11th paper (56), elderly individuals with impaired cardiac function or heart failure were evaluated.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 of these papers (2,3,(48)(49)(50)(51)(52)(53)(54)(55), patients with cancer were evaluated. In the 11th paper (56), elderly individuals with impaired cardiac function or heart failure were evaluated.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…The primary mechanisms that were evaluated or discussed included cytokines and inflammation (eight papers: 2,3,49-52,55,56); immune responses (two papers: one on eosinophils [53] and one on viral antibody [48]); activation of the sympathetic nervous system and activation of the hypothalamicpituitary-adrenal (HPA) axis (one paper: 54). Findings on the involvement of each of these four mechanisms in the development of symptom clusters are summarized below.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Others have measured relationship based on the effect of symptoms on outcomes 3. Most agree that SCs have a greater adverse impact on outcomes than individual symptoms 18 26. In one study (for the preselected symptoms of pain, fatigue and insomnia), regression analysis suggested outcome variance, for example, functional status and correlations between symptoms were tested 3.…”
Section: Discussionmentioning
confidence: 99%
“…Pain was the only symptom associated with longer survival, perhaps due to more incident pain from greater physical activity in those with better performance status. One study26 did suggest that a proposed DFP cluster was associated with disease progression in hepatobiliary cancer. They found that approximately 25% of patients experienced high levels of depression, fatigue and pain.…”
Section: Discussionmentioning
confidence: 99%
“…49, 50 Relationships between fatigue, depression and elevated eosinophil percentages have been reported in cancer research. 51 Interestingly, increased concentrations of eosinophil-selective chemokine, eotaxin, and eosinophil activation marker, eosinophil cationic protein, were observed in chronic fatigue syndrome and coronary atherosclerosis. 52, 53 This finding highlights a plausible immune-mediated inflammatory mechanism by which exhaustion may promote cardiovascular morbidity and mortality after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%